Handheld Raman Spectrometer Instrumentation for Quantitative Tuberculosis Biomarker Detection: A Performance Assessment for Point-of-Need Infectious Disease Diagnostics. Issue 7 (July 2018) - Owens, Nicholas A.; Laurentius, Lars B.; Porter, Marc D.; Li, Qun; Wang, Sean; Chatterjee, Delphi
Techniques for the detection of disease biomarkers are key components in the protection of human health. While work over the last few decades has redefined the low-level measurement of disease biomarkers, the translation of these capabilities from the formal clinical setting to point-of-need (PON) usage has been much more limited. This paper presents the results of experiments designed to examine the potential utility of a handheld Raman spectrometer as a PON electronic reader for a sandwich immunoassay based on surface-enhanced Raman scattering (SERS). In so doing, the study herein used a recently developed procedure for the SERS detection of phospho-myo-inositol-capped lipoarabinomannan (PILAM) as a means to compare the performance of laboratory-grade and handheld instrumentation and, therefore, gauge the utility of the handheld instrument for PON deployment. Phospho-myo-inositol-capped lipoarabinomannan is a non-pathogenic simulant for mannose-capped lipoarabinomannan (ManLAM), which is an antigenic marker found in serum and other body fluids of individuals infected with tuberculosis (TB). The results of the measurements with the field-portable spectrometer were then compared to those obtained for the same samples when using a much more sensitive benchtop Raman spectrometer. The results, albeit under different operational settings for the two spectrometers (e.g., signal integration time), are promising in that the limit of detection found for PILAM spiked in human serum when using the handheld system (0.18 ng/mL) approached that of the benchtop instrument (0.032 ng/mL). This work also: (1) identified potential adaptations (e.g., optimization of the plasmonically enhanced response for measurement by the handheld unit through a change in the excitation wavelength) to tighten the gap in performance; and (2) briefly examined the next steps and potential processes required to move this immunoassay platform closer to PON utility.